SHH and Notch regulate SOX9+ progenitors to govern arcuate POMC neurogenesis - Place, Elsie; Manning, Elizabeth; Kim, Dong Won; Kinjo, Arisa; Nakamura, Go; Ohyama, Kyoji (Frontiers in Neuroscience, 2022)
Pro-opiomelanocortin (POMC)-expressing neurons in the hypothalamic arcuate nucleus (ARC) play key roles in feeding and energy homoeostasis, hence their development is of great research interest. As the process of neurogenesis is accompanied by changes in adhesion, polarity, and migration that resemble aspects of epithelial-to-mesenchymal transitions (EMTs), we have characterised the expression and regulation within the prospective ARC of transcription factors with context-dependent abilities to regulate aspects of EMT. Informed by pseudotime meta-analysis of recent scRNA-seq data, we use immunohistochemistry and multiplex in situ hybridisation to show that SOX2, SRY-Box transcription factor 9 (SOX9), PROX1, Islet1 (ISL1), and SOX11 are sequentially expressed over the course of POMC neurogenesis in the embryonic chick. Through pharmacological studies ex vivo, we demonstrate that while inhibiting either sonic hedgehog (SHH) or Notch signalling reduces the number of SOX9+ neural progenitor cells, these treatments lead, respectively, to lesser and greater numbers of differentiating ISL1+/POMC+ neurons. These results are consistent with a model in which SHH promotes the formation of SOX9+ progenitors, and Notch acts to limit their differentiation. Both pathways are also required to maintain normal levels of proliferation and to suppress apoptosis. Together our findings demonstrate that hypothalamic neurogenesis is accompanied by dynamic expression of transcription factors (TFs) that mediate EMTs, and that SHH and Notch signalling converge to regulate hypothalamic cellular homoeostasis.